TINJAUAN YURIDIS TERHADAP TINDAK PIDANA BERITA HOAX PENYEBARAN KEBENCIAN - Muhammad Feby Andreawan; Safik Faozi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
This study describes the formulation of the problem. The data analysis technique used in this study consists of a deductive comparative analysis that begins with a general statement that is known to exist and ends with a more specific conclusion. From the results of the examination, Law Number 19 of 2016 which regulates Electronic Information and Transactions was born, namely Article Articles 27, 28 and 29, Dissemination of Fake News. Criminal liability for perpetrators of spreading fake news can be punished based on the elements as referred to in Article 28 of Law Number 19 of 2016 concerning Digital Information and Electronic History, namely Article 28(1). The suspect can be sentenced/punished with a maximum imprisonment of 6 years and/or up to 1,000,000,000 (billion rupiah) for the fine. The public for the proposed law in Indonesia to allow the government to eradicate fake news that circulates freely on various social media channels, especially Facebook. For the sake of the people, I hope that the Indonesian people will be smarter in choosing and categorizing all the news that appears on social media today.